Behavioural economics vs social practice theory: perspectives from inside the United Kingdom government - Hampton, S; Adams, R (Elsevier, 2018)
This paper contributes to the ongoing debate on the role of the social sciences in influencing energy and environmental policy. It presents the views of research professionals inside government on the apparent stand-off between proponents of behavioural economics and adopters of social practice theory in academic energy research. Drawing on auto-ethnographic insights and interviews with government social researchers (GSRs) working on energy and climate change, we chart the rise of behavioural economics within the UK government, discussing the reasons behind its success, and its limitations. GSRs’ perspectives on energy research using practice theory are presented, juxtaposed with arguments which help to explain why policy engagement is not a ubiquitous ambition for all energy researchers. We find that government social researchers actively engage with a range of theoretical approaches and social scientific methods. They express enthusiastic interest in research using practice theory, but point to a need for applicable evidence if they are to use it in their own practice. Applying insights from the two theories themselves, we tentatively suggest ways in which GSRs could help, and be helped, to incorporate practice theory into mainstream policy discourse.